Honey, Crocus-Sativus-Linnaeus, and Clitoria-Ternatea Improve the Elderly’s Quality of Life and Sleep Quality in Yogyakarta - Hidayati, Rizqi Wahyu; Sukmawati, Anastasia Suci; Astuti, Yuli (Jurnal Kesehatan Masyarakat, 2024)
Older adults have sleep disorders that lead to decreased quality of life and risk of chronic disease complications. Older adults need to improve their sleep quality to gain a better quality of life. They aimed to investigate the effectiveness of Crocus-sativus-Linnaeus and Clitoria-Ternatea in enhancing the quality of life and sleep of older adults. The quasi-experiment with a control group design was used. The 40 elder adults with hypertension, without dementia, severe cardiovascular disease, and hypersensitivity to compounds; were recruited. The tools were PSQI and WHO-QL. Analysis used t-test and Wilcoxon test. Crocus-sativus-Linnaeus and Clitoria-Ternatea were insignificant in improving sleep quality p = 0.264 (p0.05) and physical domain in quality-of-life p = 0.075. It significantly improved the quality of life in the psychological, social relationships, and the environment, with p = 0.007, p = 0.003, and p = 0.041. For Future research increasing the number of samples is needed.